«От автора» к читателю «Братьев Карамазовых» Тайна, чудо и авторитет – герменевтическая перспектива в предисловии романа - КРОО, КАТАЛИН (SlavVaria, 2021)
“From the Author” to the Reader of The Brothers Karamazov. Mystery, Miracle and Authority – Hermeneutic Perspectives in the Preface to the Novel. The paper offers new aspects to the critical reading of the widely interpreted preface “From the Author” in Dostoevsky’s novel The Brothers Karamazov. Giving a synthesis of the historical, narratological and rethorical perspectives in the interpretation of the given text, this new approach enters a systematic metapoetic explanation. The semantic units examined lead to the triple motif construction, familiar from “The Grand Inqusitor” – mystery, miracle and authority. It is mystery that stands at the focus of the examination within the problem context of cognition, understanding, interpretation. The internally contradictory idea of elucidating something which is still unclear is projected upon such time concepts as pred – post, beginning – end, the actual moment and processuality. These motifs make reference both to the modelled reality and the modelling literary discourse, metapoetically setting a reading strategy for the recipient.